RESEARCH OF CASM’S MANAGEMENT QUALITY ACCORDING TO THE THEORY OF FARRO CUSTODIO - Inga Arias, Miguel Gerardo (2014)
TThis paper presents an investigation based on the Evaluation of Management Quality, within the framework of Educational Quality. It was based on the instrument created by Dr. Farro Custodio, adapted to the characteristics of the evaluated Institution, the Colegio de Aplicacion San Marcos (CASM). Its dependency on the Faculty Education allowed fast and easy access, to documentation, and premises, interviews with students, teachers, administrative and managing staff. We present the theoretical framework, CASM characteristics, indicators, instrument application results analysis and an improvement plan. Finally, we present some graphs.